A perfect storm: how high levels of risk and weak internal controls resulted in violations of the foreign corrupt practices act. Issue 3 (9th July 2021) - Franz, Diana
Abstract : Theoretical basis: This case is based on Weatherford International's settlement with the Securities and Exchange Commission (SEC) and the Department of Justice (DOJ). Both the SEC and the DOJ were critical of Weatherford for its violations of the Foreign Corrupt Practices Act and for its "inadequate internal controls." This case explores the Foreign Corrupt Practices Act (FCPA) violations and issues related to internal controls. Research methodology: Case study. Case overview/synopsis: This case is based on Weatherford International's settlement with the SEC and the Department of Justice. Weatherford provided equipment and services in the oil and gas industry. Because international markets were growing faster than domestic markets, Weatherford made a strategic decision to pursue growth in international markets. The oil and gas industry has high levels of operating risk as did the countries that Weatherford decided to pursue operations in. However, despite the decision to take on additional risk, Weatherford failed to implement adequate systems of internal controls. The title of the case "A Perfect Storm" refers to Weatherford's trifecta of operating in an industry with high levels of corruption risk, countries with high levels of corruption risk and failing to implement adequate internal controls despite those high operating risks (Department of Justice, 2013 ). Weatherford was ultimately assessed a 152m penalty for its violations of the FCPA that included bribery, volume discounts, improper payments and kickbacks. Complexity academic level: Undergraduate and graduate auditing classes.